Anonymous empire : a study of the lobby in Great Britain - Finer, S. E. (London, 1958)
What is 'The Lobby'? Look at any daily newspaper, and will find this sort of item: you British Furniture Manufacturers' Federated Association wants to close down the industry's Develop ment Council. The Institute of Directors is urging the Chancellor to reduce surtax. The National Union of Retail Confectioners is protesting against the Shops Bill; the Caterers' Association wants it dropped; while the National Chamber of Trade is insistent that 'the organized retailers of Britain are anxious for the Bill to be adopted'. The Federation of British Industries wants 'radical cuts in public spending', and the Birmingham Chamber of Commerce accuses the Board of Trade and the Ministry of Supply of favouritism towards the Development Areas.
Keywords: Lobbying - Great Britain